2016
DOI: 10.1073/pnas.1602618113
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical DNA-binding mode of repressor and its disassembly by antirepressor

Abstract: DNA-binding repressors are involved in transcriptional repression in many organisms. Disabling a repressor is a crucial step in activating expression of desired genes. Thus, several mechanisms have been identified for the removal of a stably bound repressor (Rep) from the operator. Here, we describe an uncharacterized mechanism of noncanonical DNA binding and induction by a Rep from the temperate Salmonella phage SPC32H; this mechanism was revealed using the crystal structures of homotetrameric Rep (92–198) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…We show that CID58 binds to adjacent half-sites on the palindromic O L , with a decrease in the average distance between the NTDs. Thus, we show unequivocally that TP901-1 CI binds canonically to DNA, unlike, for example, suggested for the Salmonella phage Rep, where the current hypothesis is that two monomers from different dimers in a tetramer bind to adjacent DNA half-sites [40].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We show that CID58 binds to adjacent half-sites on the palindromic O L , with a decrease in the average distance between the NTDs. Thus, we show unequivocally that TP901-1 CI binds canonically to DNA, unlike, for example, suggested for the Salmonella phage Rep, where the current hypothesis is that two monomers from different dimers in a tetramer bind to adjacent DNA half-sites [40].…”
Section: Discussioncontrasting
confidence: 67%
“…We sought to identify additional helical hook dimers of transcription factors and regulators by a new PHYRE2 search and visual inspection of members of the Cd00093 HTH_XRE family in the Conserved Domain Database (CDD) , into which the NTD of TP901‐1, Li TR, Cd TR and Cc RM are classified: BswR , a dimeric controller of motility and biofilm formation in Pseudomonas aeruginosa (PDB entry: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=4O8B), and a repressor protein from Salmonella temperate phage (PDB entry: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5D4Z) could be additionally found . The latter can be considered a helical hook dimer containing a short (170–175) and a long (178–196) helix connected by a short loop.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the exact composition of hcGAS-N160 and the DNA ligand, we used SEC-MALS to determine the exact molecular mass of our proteins and complex, as SEC-MALS has previously been shown to be useful for this purpose (28,29). The results showed that hcGAS-N160 is a monomer with molecular mass 17.78 6 0.456 kDa (Supplemental Fig.…”
Section: Dna Binding By Hcgas-n160 Induces Secondary Structural Changmentioning
confidence: 96%
“…Size-exclusion chromatography with multiangle light scattering (SEC-MALS) experiments were performed using a fast protein liquid chromatography system (GE Healthcare) connected to a Wyatt Mini-DAWN TREOS MALS instrument and a Wyatt Optilab rEX differential refractometer (28,29). Indicated proteins at 2.0 mg/ml with or without incubation with DNA for 30 min were injected into a Superdex 75-column equilibrated in buffer C [20 mM Tris-HCl (pH 7.6) and 100 mM NaCl].…”
Section: Size-exclusion Chromatography With Multiangle Light Scatteringmentioning
confidence: 99%
“…Repressors of other phages, for example, that of coliphage 186, are, by contrast, inactivated via protein-protein interactions with small antirepressor proteins (Shearwin et al, 1998). In these cases, production of the antirepressor is frequently controlled by a LexA-regulated promoter, and thus, despite different mechanisms, as in phage lambda, repressor inactivation is induced by the host SOS response (Heinzel et al, 1992;Kim et al, 2016;Lemire et al, 2011;Mardanov and Ravin, 2007;Quinones et al, 2005;Shearwin et al, 1998). Unlike autoproteolytic repressors, however, the mechanisms underlying antirepressor-mediated inactivation of phage repressors have seldom been fully characterized and it is possible that a given antirepressor can function by more than one mechanism.…”
Section: Introductionmentioning
confidence: 99%